Pengaruh Kualitas Pelayanan Terhadap Keputusan Pembelian - Novita Djafar; Irwan Yantu; Sudirman Sudirman; Raflin Hinelo; Roy Hasiru (State University of Gorontalo, 2023)
The purpose of this research was to determine to what extent service quality affected purchase decisions at Cv. Mufidah, Gorontalo City.” This research employed a quantitative approach using a quantitative correlational method with a sample size of 30 consumers. Besiders, the data collection techniques used in this research were interviews, questionnaires, and documentation, while the data analysis technique was simple regression analysis. The research finding denoted that there was a positive and significant effect of service quality on purchase decisions at CV Mufidah, Gorontalo City.” The effect of service quality on purchase decisions reached 43%, while the remaining 57% was affected by other variables that were not examined in this research.